2020
DOI: 10.1177/1535676020926968
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde Vapor Characteristics in Varied Decontamination Environments

Abstract: Introduction: This effort investigated formaldehyde vapor characteristics under various environmental conditions by the analyses of air samples collected over a time-course. This knowledge will help responders achieve desired formaldehyde exposure parameters for decontamination of affected spaces after a biological contamination incident. Methods: Prescribed masses of paraformaldehyde and formalin were sublimated or evaporated, respectively, to generate formaldehyde vapor. Adsorbent cartridges were used to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Findings from other studies have shown that the effects of formalin contamination on microbes are also affected by environmental conditions one of which is air temperature. Previous research has shown that low temperatures (approximately 10 0 C) reduce the formaldehyde concentration in the air while the formaldehyde concentration at ambient temperature (approximately 22 0 C) is still higher than at low temperatures (Choi et al, 2021). A similar study also reported the efficacy of formaldehyde in laboratory decontamination with type BSL-3 by formaldehyde fumigation.…”
Section: Levels Of Formaldehyde Vs Colony Bacteriamentioning
confidence: 75%
“…Findings from other studies have shown that the effects of formalin contamination on microbes are also affected by environmental conditions one of which is air temperature. Previous research has shown that low temperatures (approximately 10 0 C) reduce the formaldehyde concentration in the air while the formaldehyde concentration at ambient temperature (approximately 22 0 C) is still higher than at low temperatures (Choi et al, 2021). A similar study also reported the efficacy of formaldehyde in laboratory decontamination with type BSL-3 by formaldehyde fumigation.…”
Section: Levels Of Formaldehyde Vs Colony Bacteriamentioning
confidence: 75%
“…However, surface porosity is not the sole factor influencing the effective dose at the surface of a material; further work would be required to verify the effect of surface roughness (effecting formulation wetting), organic content (material demand could reduce available formalin for spore interaction) or the effect of different meteorological conditions (temperature, humidity and solar irradiation) on the hazard reduction levels achieved employing the above application regimes. Such environmental and surface chemical demand factors have been studied under controlled test chamber conditions to determine their effect on the concentration of formalin when applied as a vapour for biological decontamination (Choi et al, 2021). In that study, there was no discolouration or change in physical appearance of material coupons (painted cinder block concrete and bare pine wood) or test chamber components upon formalin vapour exposure (Choi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Such environmental and surface chemical demand factors have been studied under controlled test chamber conditions to determine their effect on the concentration of formalin when applied as a vapour for biological decontamination (Choi et al, 2021). In that study, there was no discolouration or change in physical appearance of material coupons (painted cinder block concrete and bare pine wood) or test chamber components upon formalin vapour exposure (Choi et al, 2021). The chemical compatibility of formalin is greater across a wide range of material types (polymers, metals, rubber) than common oxidant decontaminants, such as sodium hypochlorite (Cole Palmer Chemical Compatibility Database, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…4) Cross Correlation: There were some interdependence observed in the independent variables especially between temperature and formaldehyde emissions from the formalin container due to environment dependent adsorption properties of formaldehyde on surfaces because of its high dipole moment [50]- [52]. Due to these interdependencies there was some correspondence between the variation of these 'independent variables' which have to be taken into account while evaluating the data.…”
Section: Sampling Strategy For Experimental Datamentioning
confidence: 99%